2013
DOI: 10.1161/atvbaha.113.301627
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Circulating DNA and Chromatin Are Independently Associated With Severe Coronary Atherosclerosis and a Prothrombotic State

Abstract: OBJECTIVE Aberrant neutrophil activation occurs during the advanced stages of atherosclerosis. Once primed, neutrophils can undergo apoptosis or release neutrophil extracellular traps (NETs). This extracellular DNA exerts potent pro-inflammatory, prothrombotic and cytotoxic properties. The goal of this study was to examine the relationships between extracellular DNA formation, coronary atherosclerosis and the presence of a prothrombotic state. APPROACH AND RESULTS In a prospective, observational, cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
332
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 376 publications
(351 citation statements)
references
References 50 publications
14
332
0
5
Order By: Relevance
“…Extracellular nucleosomes and dsDNA have been proposed as surrogate markers for NET burden. 20 We found both nucleosomes and dsDNA to be highly increased in CLS plasma compared with femoral plasma. Moreover, CLS nucleosomes and dsDNA levels correlated positively with thrombus NET burden, which suggests that in STE-ACS, circulating nucleosomes and ds-DNA primarily originate from NETs.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Extracellular nucleosomes and dsDNA have been proposed as surrogate markers for NET burden. 20 We found both nucleosomes and dsDNA to be highly increased in CLS plasma compared with femoral plasma. Moreover, CLS nucleosomes and dsDNA levels correlated positively with thrombus NET burden, which suggests that in STE-ACS, circulating nucleosomes and ds-DNA primarily originate from NETs.…”
Section: Discussionmentioning
confidence: 68%
“…20 Nucleosomes were significantly increased at the CLS Figure 5A) correlated positively with coronary thrombus NET burden.…”
Section: Surrogate Markers Of Nets Are Increased At the Cls And Corrementioning
confidence: 93%
“…13,14 Of interest, plasma MPO-DNA complexes, considered a marker of NETs, were recently associated with the severity of coronary atherosclerosis in humans and occurrence of major adverse cardiac events. 42 Moreover, neutrophil elastase present on NETs 13 catalyzes the breakdown of collagen (type III and IV), fibronectin, and proteoglycans during MI, 10 which could further hinder efficient myocardial repair. Histone citrullination is necessary for chromatin decondensation during NET formation.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 The importance of these structures has been described in various diseases, including infection-associated thrombosis, 10 small vessel vasculitis, 11 systemic lupus erythematosus (SLE), [12][13][14] and skin inflammation 15 (Table). A current study has shown that NET fragments may serve as indicators of cardiovascular inflammation, 16 while we could elucidate a mechanism of NET-driven atherogenesis involving the autoimmune activation of plasmacytoid dendritic cells. 9,17 Mechanistically, complexes of self-DNA (presumably NET-borne DNA, but also self-DNA from dying cells) and neutrophil-derived granule proteins (eg, cathelicidin) stimulate plasmacytoid dendritic cells in the vessel wall, resulting in a strong type I interferon response, which drives atherogenesis.…”
mentioning
confidence: 90%